2009
DOI: 10.1038/sj.bjc.6605340
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling associated with the progression to poorly differentiated thyroid carcinomas

Abstract: BACKGROUND: Poorly differentiated thyroid carcinomas (PDTC) represent a heterogeneous, aggressive entity, presenting features that suggest a progression from well-differentiated carcinomas. To elucidate the mechanisms underlying such progression and identify novel therapeutic targets, we assessed the genome-wide expression in normal and tumour thyroid tissues. METHODS: Microarray analyses of 24 thyroid carcinomas -7 classic papillary, 8 follicular variants of papillary (fvPTC), 4 follicular (FTC) and 5 PDTC -w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 45 publications
5
53
0
Order By: Relevance
“…The authors demonstrated that the Polo-like kinase 1 (PLK1), previously included in the 'proliferation cluster' and 'chromosomal instability 70 cluster' (Tabach et al 2005, Carter et al 2006, Whitfield et al 2006, was required for ATC cell proliferation and cell survival, and this dependence was not detected in normal thyroid cells, in agreement with the data of Nappi et al (2009). Pita et al (2009) found a number of upregulated cell cycle-related genes in PDTC. Among them were genes associated with mitosis such as CDC28 protein kinase regulatory subunit 2 (CKS2) and cyclin E2 (CCNE2), which were previously reported as upregulated in many other types of tumors (Gudas et al 1999, Scrideli et al 2008.…”
Section: Transcriptome Of Pdtc and Undifferentiated Thyroid Cancer Insupporting
confidence: 58%
“…The authors demonstrated that the Polo-like kinase 1 (PLK1), previously included in the 'proliferation cluster' and 'chromosomal instability 70 cluster' (Tabach et al 2005, Carter et al 2006, Whitfield et al 2006, was required for ATC cell proliferation and cell survival, and this dependence was not detected in normal thyroid cells, in agreement with the data of Nappi et al (2009). Pita et al (2009) found a number of upregulated cell cycle-related genes in PDTC. Among them were genes associated with mitosis such as CDC28 protein kinase regulatory subunit 2 (CKS2) and cyclin E2 (CCNE2), which were previously reported as upregulated in many other types of tumors (Gudas et al 1999, Scrideli et al 2008.…”
Section: Transcriptome Of Pdtc and Undifferentiated Thyroid Cancer Insupporting
confidence: 58%
“…PROX1 downregulation in thyroid cancers was also confirmed using another set of thyroid cancer gene profiling study (Figure 1B) (12). Moreover, we performed analyses against additional public repositories (1316) to investigate PROX1 expression through NextBio Disease Atlas (9) and consistently found PROX1 downregulation in various thyroid cancers (Figure 1C). Moreover, PROX1 mRNA level was compared in PTCs vs. their adjacent normal tissues from the same patients using Gene Expression Omnibus (GEO) statistical tool against two independent data sets (GSE3467, GSE3678), which revealed PROX1 downregulation in PTCs relative to their matched normal tissues (Figure 1D,E).…”
Section: Resultsmentioning
confidence: 90%
“…Other pathway showing important alterations was TGFbeta signalling pathway, associated with the epithelial-to-mesenchymal transition characteristic for less differentiated, advanced cancers (Grande et al 2002). Other observations from microarray analysis also supported the hypothesis of progression from well to poorly differentiated thyroid cancers (Pita et al 2009), suggesting that poorly differentiated cancers had expression profile closer to PTC, especially its follicular variant, than to FTC. The group of Santoro, by analysis of gene expression profile of anaplastic cancer, indicated on new potential molecular targets useful for therapy, among them POLO kinase (Nappi et al 2009).…”
Section: Poorly Differentiated and Undifferentiated Thyroid Cancersmentioning
confidence: 56%